2022
DOI: 10.1007/s41999-021-00600-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on hip fracture care in Ireland: findings from the Irish Hip Fracture Database

Abstract: Key summary points Aim To identify the impact of COVID-19 on case-mix, care standards and outcomes of hip fracture patients in Ireland for the first 6 months of the COVID-19 pandemic. Findings There was a 15% reduction in admissions per month during the first 6 months of the COVID-19 pandemic. There was a reduction in compliance with many of the Irish Hip Fracture Standards following the COVID-19 pandemic. Message Every attempt s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Likewise, the LOS in the hospital, and hospitalization/mortality rates in the ED were similar in the pandemic (25.8%) and pre-pandemic periods (22.8%) in the present study whereas mortality rates in ED at both periods were quite low. In a study from Ireland, there were reductions in admissions, and compliance with many of the Irish Hip Fracture Standards, LOS during the pandemic, but in-hospital mortality was similar in pre-pandemic and pandemic periods [41]. In contrary, in a meta-analysis, it was shown that COVID-19 increased the risk of mortality in patients with hip fractures [42].…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, the LOS in the hospital, and hospitalization/mortality rates in the ED were similar in the pandemic (25.8%) and pre-pandemic periods (22.8%) in the present study whereas mortality rates in ED at both periods were quite low. In a study from Ireland, there were reductions in admissions, and compliance with many of the Irish Hip Fracture Standards, LOS during the pandemic, but in-hospital mortality was similar in pre-pandemic and pandemic periods [41]. In contrary, in a meta-analysis, it was shown that COVID-19 increased the risk of mortality in patients with hip fractures [42].…”
Section: Discussionmentioning
confidence: 97%
“…da Silva et al 9 found that the incidence of hip fracture patients over 60 years of age decreased in 2020 compared to 2019 in the analysis of the Brazilian public health care system. Brent et al 8 reported that hip fracture incidence in 2020 decreased by 15% compared to that in 2019 in the analysis of the Irish Hip Fracture Database. Because the lockdown period differed in each country and there are differences in ethnic, region and medical policy, the various results of these studies should not be simply compared and should not be interpreted as general trends in COVID pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 21 26 27 In addition, comparative studies of mortality rates of hip fracture with COVID-19 negative before and after the COVID-19 pandemic reported no significant increase in the mortality rate. 8 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, two days is the recommended time limit for patient presentation for hip surgery, especially when the patient is 65 years old or older. Brent et al [34] observed a 15% reduction in admissions for hip surgery and a decrease in compliance with many sur-gery standards following the COVID-19 pandemic in Ireland. In Portugal, the hip surgery rate beyond the appropriate time was, on average, 54.4% (2017-2019), 53.0% (2020), and 51.1% (2021-2022), without expressive differences.…”
Section: U4 Number Of Hip Surgeries Beyond 48h After Fracturementioning
confidence: 99%